THE EFFECT OF PRINCIPAL LEADERSHIP AND TEACHERS’ PERFORMANCE ON THE QUALITY OF EDUCATION AT JUNIOR HIGH SCHOOL LEVEL - Suhartono Suhartono; Sartiah Yusran; Sahlan Sahlan (Journal of Language Education and Educational Technology (JLEET), 2020)
The quality of education is the ultimate goal of a teaching and learning process. This study aimed to finding out a significant influence of principal leadership and teachers’ performance on the quality of education at Junior High School level and to identify dominant factors affecting the quality of education. This research was conducted in Junior High School in Konawe regency. This is a mix method research using a survey for quantitative data and observations as well as interview for qualitative data. The primary data was collected from 88 respondents, while the secondary data was from related documents. This study revealed that 1) there was a significant influence of principal leadership on the quality of education at Junior High School level. Based on significance test, it was obtained that t value counted for 5.486 compared with table t values with probability 0.05 of 1,991 where the value of t count ≥ t table then Ho1 rejected; 2) there was a significant influence of teachers’ performance on the quality of education. Based on its significance test, it was obtained that t value counted for 2.306 ≥ t table value of 1,991 where t count ≥ t table then Ha2 accepted; 3) there was a significant influence simultaneously between principal leadership and teachers’ performance on the quality of education. It was based on Anova Test results that F count was 18,955 with significance level 0,000 < probability value α 0.05 while F table according to the level of significance 0.05 (2;86) of 3.10 so that F counted > F table (18,955 > 3.10), therefore, Ho3 rejected. The contribution of the principal leadership variable and teacher’s performance on the quality of education was 30,8%. In order to achieve a quality of better education, principal and teachers should develop their professional skills.